Presynaptic Striatal Dopaminergic Function in Atypical Parkinsonism: A Metaanalysis of Imaging Studies - Valtteri Kaasinen; Tuomas Kankare; Juho Joutsa; Tero Vahlberg (SOC NUCLEAR MEDICINE INC, 2022)
Background: Multiple-system atrophy (MSA), progressive supranuclear palsy (PSP), and corticobasal syndrome (CBS) have signs and symptoms overlapping those of Parkinson disease (PD), complicating their clinical diagnosis. Although presynaptic dopaminergic brain imaging with PET and SPECT is clinically widely used for patients with suspected PD, the benefit of functional imaging in atypical parkinsonism syndromes remains unclear. We compared striatal presynaptic dopaminergic function in MSA parkinsonism variant (MSA-P), MSA cerebellar variant (MSA-C), PSP, CBS, and PD using combined quantitative data from all published studies. Methods: The PubMed database was searched from inception to August 2018 for the terms "dopamine" OR "dopaminergic" AND "PET" OR "SPECT" OR "SPET" and keywords related to PD, MSA, PSP, and CBS. In total, 1,711 publications were identified. PET or SPECT studies comparing patients with atypical parkinsonism to another diagnostic group (PD, MSA, PSP, or CBS) were included. Tracers for dopamine transporter (DAT), aromatic amino acid decarboxylase (AADC), or vesicular monoamine type 2 were investigated. Tracer binding data were extracted from the original articles. Heterogeneity of the data was examined using I-2 statistics, and a random-effects model was used to summarize data. Hedges g was used as an estimator of effect size in group comparisons. Results are reported according to PRISMA guidelines.
Results: Thirty-five studies (29 DAT, 6 AADC, no vesicular monoamine type 2 studies) with 356 MSA-P patients, 204 PSP patients, 79 CBS patients, and 62 MSA-C patients were included in the meta-analysis. Caudate nucleus and putamen DAT function was clearly lower in PSP than in PD (caudate: 34.1% difference, g = -1.08, 95% confidence interval [CI] = -1.52 to -0.64; putamen: 18.2%, g = -0.86, 95% CI = -1.50 to -0.21) and MSA-P (striatum: 31.4%, g = -0.70, 95% CI = -1.21 to -0.19) and was clearly lower in MSA-P than in MSA-C (striatum: 46.0%, g = 1.46, 95% CI = 0.23 to 2.68). Although not significant because of limited data, aromatic L-AADC results paralleled the DAT findings.
Conclusion: Striatal presynaptic DAT function is clearly lower in PSP patients than in PD and MSA-P patients and is clearly lower in MSA-P patients than in MSA-C patients.